Internal audit functions and audit outcomes: Evidence from Indonesia - Achmad Dzulfikar Dzikrullah; Iman Harymawan; Melinda Cahyaning Ratri (Cogent Business & Management, 2020)
The internal audit function is important to minimize the occurrence of fraudulent financial statements and provide assurance and independent consultation for decision-making. The purpose of this study is to analyze the relationship of the quality of internal audit team (internal audit function) on audit fees, audit quality, audit choice, and audit opinion. This study uses 722 observations on companies listed on the Indonesia Stock Exchange for two periods from 2016 to 2017 and uses Ordinary Least Square Regression analysis techniques to examine the hypotheses. This study found that one of the internal auditors' functions, which is size of the internal audit team, as a corporate oversight mechanism has a positive and significant relationship to the magnitude of external auditor fees, audit quality, and the tendency of companies to choose auditors with big names (Big4). In addition, this study found that internal audit also has a negative and significant influence on the tendency of companies to accept going concern audit opinions. This research provides support on the benefit of having a good quality of internal auditors for the company. The results of this study indicate that companies that have an adequate internal audit function tend to cost higher external auditor fees, and hiring auditors with big names (Big4) to produce high audit quality. In addition, the existence of adequate internal auditors also reducing the probability of the firms on receiving the going concern audit opinions.
Keywords: M41; M42; 650; Internal audit; audit fee; audit quality; audit choice; audit opinion